Trends in Tuberculosis Prevalence in the Work Area of Waepandan Community Health Center from 2022 to 2025: Tuberculosis Prevalence Trends in Waepandan (2022–2025) - Lainuru, Indriyati; Fajar, Harianti (CV. Paperhome Indonesia, 2025)
Background: Tuberculosis (TB) remains one of the most prevalent infectious diseases globally. It is caused by Mycobacterium tuberculosis, which is transmitted through airborne droplets. In the Waepandan Community Health Center coverage area, there were 2 confirmed TB cases out of 4 suspected cases in 2022. This number increased significantly to 11 confirmed cases from 20 suspected cases in 2025, indicating a concerning rise in incidence. Methods: This study used a quantitative approach with a descriptive design. The sampling technique was total sampling, involving all individuals who were suspected of having tuberculosis in the work area of Waepandan Health Center in 2025. Results: The analysis showed an increase in both the number of suspected and confirmed TB cases over the study period. This trend suggests a growing public health concern that requires immediate and targeted prevention strategies. Conclusion: The rising number of TB cases in the Waepandan Health Center area highlights the need to strengthen early detection, community education, and environmental health interventions. Preventive efforts must be enhanced to control TB transmission effectively.